Long-term safety and immunogenicity of an MF59-adjuvanted spike glycoprotein-clamp vaccine for SARS-CoV-2 in adults aged 18–55 years or ≥56 years: 12-month results from a randomised, double-blind, placebo-controlled, phase 1 trialResearch in context - Keith J. Chappell; Francesca L. Mordant; Alberto A. Amarilla; Naphak Modhiran; Benjamin Liang; Zheyi Li; Danushka K. Wijesundara; Julia A. Lackenby; Paul Griffin; Jillian K. Bennet; Luca Hensen; Wuji Zhang; et al. (EBioMedicine, 2023)
Summary: Background: We previously demonstrated the safety and immunogenicity of an MF59-adjuvanted COVID-19 vaccine based on the SARS-CoV-2 spike glycoprotein stabilised in a pre-fusion conformation by a molecular clamp using HIV-1 glycoprotein 41 sequences. Here, we describe 12-month results in adults aged 18–55 years and ≥56 years. Methods: Phase 1, double-blind, placebo-controlled trial conducted in Australia (July 2020–December 2021; ClinicalTrials.gov NCT04495933; active, not recruiting). Healthy adults (Part 1: 18–55 years; Part 2: ≥56 years) received two doses of placebo, 5 μg, 15 μg, or 45 μg vaccine, or one 45 μg dose of vaccine followed by placebo (Part 1 only), 28 days apart (n = 216; 24 per group). Safety, humoral immunogenicity (including against virus variants), and cellular immunogenicity were assessed to day 394 (12 months after second dose). Effects of subsequent COVID-19 vaccination on humoral responses were examined. Findings: All two-dose vaccine regimens were well tolerated and elicited strong antigen-specific and neutralising humoral responses, and CD4+ T-cell responses, by day 43 in younger and older adults, although cellular responses were lower in older adults. Humoral responses waned by day 209 but were boosted in those receiving authorised vaccines. Neutralising activity against Delta and Omicron variants was present but lower than against the Wuhan strain. Cross-reactivity in HIV diagnostic tests declined over time but remained detectable in most participants. Interpretation: The SARS-CoV-2 molecular clamp vaccine is well tolerated and evokes robust immune responses in adults of all ages. Although the HIV glycoprotein 41-based molecular clamp is not being progressed, the clamp concept represents a viable platform for vaccine development. Funding: This study was funded by the Coalition for Epidemic Preparedness Innovations, the National Health and Medical Research Council of Australia, and the Queensland Government.